Exhibiting Abstraction: Strategies in the Propagation of an Avant-garde 1908–1915 - Bartosch, Christina (De Gruyter, 2025)
The time around 1910 has entered art history as the moment when «abstraction was invented». However, where and when works of non-figurative art became present in the public eye has been afforded little attention to date. Exhibiting Abstraction is the first publication to be devoted entirely to the presentation of abstract art between 1908 and 1915 and as such uncovers strategies for the dissemination of early abstract painting in exhibitions. Die Zeit um 1910 ist als Zeitpunkt der „Geburt der Abstraktion“ in die Kunstgeschichte eingegangen. Doch wo und wann Werke der nicht-figurativen Kunst öffentlich sichtbar wurden, ist bisher kaum beachtet worden. Exhibiting Abstraction ist die erste Publikation, die sich der Präsentation abstrakter Kunst zwischen 1908 und 1915 widmet und dabei Strategien zur Verbreitung der frühen abstrakten Malerei in Ausstellungen aufdeckt.